Impact of Foreign Direct Investment on Renewable Energy Consumption: Findings from Bootstrap ARDL with a Fourier Function - Telatar, Osman Murat; Adimli, Tugce (International Journal of Energy Economics and Policy, 2024)
Renewable energy consumption (REC) is viewed to be a core component for delivering sustainable economic growth. It is broadly acknowledged that REC can significantly contribute to lessening the burden of carbon emissions on the environment and fostering economic progress. Although foreign direct investments (FDI) are perceived as a key catalyst of REC growth, in some cases they can cause negative effects on REC. While there are many studies in the literature exploring the effects of FDI on variables such as economic growth, employment and foreign exchange deficits, the amount of studies examining the effect of the said variable on REC is very limited. The existing study attempts to fill this knowledge gap concerning the relationship between FDI and REC in Türkiye. This research investigates the long-run impact of FDI on RECs in Türkiye for the period 1973-2022 using the bootstrap Fourier ARDL technique. Empirical analysis reveals that FDI affects REC negatively, while GDP has no effect. The study’s conclusions confirm the Pollution Haven Hypothesis (PHVH) in Türkiye, suggesting that the country has emerged as a desirable destination for businesses seeking to relocate their operations and evade the strict environmental regulations in their home countries.